IMPROVE THE COORDINATION OF EYE AND HAND MOTION THROUGH BOWLING GAME FOR CHILDREN TUNAGRAHITA ARE CLASSES VI SLB YPAC EKONOMI - Desmianti - Mimi (Universitas Negeri Padang, 2012)
This research was conducted based on the problems that were discovered in West Sumatra, SLB YPAC tunagrahita was the eighth grade children misbehaving motion eye and hand coordination. From the results of the identification and esesment of researchers did on children, children experiencing obstacles in his life. In the process of pembalajaran teachers less paying attention, because students who exceed the capacity of the class and time limitations. Based on this research aims to improve the coordination of eye and hand motion tunagrahita child being through bowling game.This research uses experimental approach in the form of single subject research (SSR) with A-B design. The subject of this research was the son of tunagrahita was. Behaviornya Target motion coordination is the ability of the eye and hand in playing bowling. Starting from seeing the condition as much as five times the baseline observations and continued with the intervention by as much as eight times.The results of this research show that, of children in play bowling ability increases. Baseline conditions of five times the child observation is just doing one item only. On the conditions childrens intervention can do kagiatan up to 4 items. Thus the hypothesis has been proposed before, meaning that the game received a bowling motion coordination capabilities can enhance the eyes and hands of children are tunagrahita. From this research are expected to be useful for teachers, parents, and further research and guidelines for improving coordination be motion eye and hand over the bowling game.